Sports Cardiology - Egger F; Ukaj A (Dynamic Media Sales Verlag, 2023)
Problem and objective: To inform about the incidence, causes and prevention measures of sudden cardiac death in sports. Methods: A literature search was performed (PubMed, Web of Science, Researchgate) using the terms sudden cardiac death (SCD), sudden cardiac arrest (SCA), sudden death, cardiopulmonary resuscitation, sport, exercise and athlete. Observational studies, systematic reviews and meta-analyses that examined SCD/SCA during exercise or up to one hour afterwards in recreational, competitive or elite athletes were considered.Results: Of 6350 study titles and abstracts 11 full-text studies were included in this clinical review. When the incidence was calculated based on multiple sports, it varied between populations and ranged from 0.1 to 2.9/100,000 athlete-years (AY). The incidence was highest in male professional basketball players, with 19/100,000 AY. The most frequent cause of SCD/SCA in athletes >35 years was coronary artery disease (CAD), while in younger athletes the predominating underlying pathologies (autopsy-negative sudden unexplained death, myocarditis, cardiomyopathies, coronary artery anomalies and premature CAD) differed by region. The most effective screening tool for cardiovascular disease in athletes is the ECG. Survival after CPR is substantially influenced by the use of an automated external defibrillator (AED).Discussion: SCD/SCA in athletes is a rare but very tragic event. Incidence rates in athletes differ among populations, studies, and sports. Some degree of underreporting can be assumed as there is no mandatory reporting of sports-related SCD/SCA in most countries and few scientific registries exist. Potentially, primary screening measures could be adapted to the regionally different causes of SCD/SCA. In addition, training athletes and staff in the use of an AED is paramount to improving survival rates.Key Words: Athletes, Cardiac Arrest, Cardiovascular Disease